Waste management scheme and way forward for during and post COVID-19 - Dhakal, Rabindra Prasad (Applied Science and Technology Annals, 2020)
The SARS-CoV-2 or/andCOVID-19 may have contaminated the wastes, which need especial precaution as suggested by WHO guidelines. WHO also suggested that no cases have been reported of infection from the waste workers working on infected wastes so far. However, in case of Nepal, 50% wastes used to be collected at the time 2011, which seems significantly improving as high as 81% in sampled areas. In COVID period, the concern was raised on safety issues of waste workers as suggested by RDT positive, hence, the public perception of waste management, the scope of recycling of wastes and up streaming of waste materials as economical commodities with proper intervention of technologies, awareness and behavior is incorporated in this study. It is estimated that the total Plastic wastes of major city centers could be significantly turned into useful products including fuel. For example, Kathmandu Valley can extract 24,298 KL oil from wastes plastics, which is based on calculation of waste per capita, waste composition and conversion ratio. Hence, the COVID-19 pandemic could be turn into opportunities in the sector of waste management provided we act wisely.